2023
DOI: 10.1002/cey2.340
|View full text |Cite
|
Sign up to set email alerts
|

A study of highly activated hydrogen evolution reaction performance in acidic media by 2D heterostructure of N and S doped graphene on MoOx

Abstract: Herein, a layer of molybdenum oxide (MoOx), a transition metal oxide (TMO), which has outstanding catalytic properties in combination with a carbon‐based thin film, is modified to improve the hydrogen production performance and protect the MoOx in acidic media. A thin film of graphene is transferred onto the MoOx layer, after which the graphene structure is doped with N and S atoms at room temperature using a plasma doping method to modify the electronic structure and intrinsic properties of the material. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
(119 reference statements)
0
3
0
Order By: Relevance
“…Thus, to overcome these limitations, Aydin et al developed a hybrid catalyst consisting of N and S-doped graphene and MoO x , and then analysed its activity towards the HER. 90 In this report, layered MoO x was synthesized, and then a thin film of graphene was transferred to it, followed by doping with N and S. The HER analysis showed that the as-developed hybrid catalyst showed a significantly improved catalytic performance with significantly low overpotential of 359 mV at 10 mA cm −2 compared to pure graphene and MoO x . The observed enhanced activity was attributed to the presence of oxygen in graphene, which resulted in the better electrical contact and interfacial interactions between graphene and MoO x .…”
Section: Advances In Her Applications Of N-doped Graphene (Ng) Hetero...mentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, to overcome these limitations, Aydin et al developed a hybrid catalyst consisting of N and S-doped graphene and MoO x , and then analysed its activity towards the HER. 90 In this report, layered MoO x was synthesized, and then a thin film of graphene was transferred to it, followed by doping with N and S. The HER analysis showed that the as-developed hybrid catalyst showed a significantly improved catalytic performance with significantly low overpotential of 359 mV at 10 mA cm −2 compared to pure graphene and MoO x . The observed enhanced activity was attributed to the presence of oxygen in graphene, which resulted in the better electrical contact and interfacial interactions between graphene and MoO x .…”
Section: Advances In Her Applications Of N-doped Graphene (Ng) Hetero...mentioning
confidence: 95%
“…Recently, Aydin et al developed an N- and S-doped graphene 2D heterostructure on MoOx for efficient hydrogen generation. 90 In this report, firstly graphene and MoOx were synthesized separately. For the synthesis of graphene, the thermal CVD approach was used by employing Cu foil as the growth substrate.…”
Section: Recent Advances In the Synthesis Of N-doped Graphene Heteros...mentioning
confidence: 99%
“…For the purpose of achieving high performance, the design synthesis of advanced TM@C-typed catalysts could be carried out from both carbon shell and metallic core aspects. 32 Heteroatom doping, such as the addition of nitrogen (N), 33 sulfur (S), 34 or phosphorus (P), 35,36 has been proven to be an effective avenue to engineering carbon shells. This method allows for the tuning of the electronic structure and catalytic properties of carbon by regulating the electron interaction between the heteroatoms and adjacent carbon atoms.…”
Section: Introductionmentioning
confidence: 99%